2006
DOI: 10.1111/j.1365-2133.2006.07456.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cutaneous cytomegalovirus infection in non-acquired immune deficiency syndrome, immunocompromised patients

Abstract: In non-AIDS individuals, the cutaneous lesions from CMV infection showed similar clinical and histopathological features to those of patients with AIDS. However, skin lesions may not be highly associated with HSV, and CMV does seem to contribute to lesion development as a cutaneous manifestation among the CMV infected, non-AIDS, immunocompromised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 24 publications
2
73
0
4
Order By: Relevance
“…However, the skin may be the initial site of CMV involvement and may provide the first clue to systemic infection. A wide spectrum of cutaneous lesions associated with CMV infection has been reported, including morbilliform eruptions, purpura, vesiculobullous lesions, nodules, papular eruptions, verrucous lesions and ulcerations 9,10 , but to date no case of SJS has been related to this infectious agent. In our case a possible association between CMV and SJS is suggested by a temporal relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the skin may be the initial site of CMV involvement and may provide the first clue to systemic infection. A wide spectrum of cutaneous lesions associated with CMV infection has been reported, including morbilliform eruptions, purpura, vesiculobullous lesions, nodules, papular eruptions, verrucous lesions and ulcerations 9,10 , but to date no case of SJS has been related to this infectious agent. In our case a possible association between CMV and SJS is suggested by a temporal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…necrosis factor agents, thalidomide, cyclosporine, cyclophosphamide, N-acetylcysteine and other modalities such as plasmaferesis, have been tried along with supportive measures, but with variable results 10 . In 1998, on the basis of the identification of the mechanism of keratinocytes apoptosis in SJS and TEN, a therapy approach based on the use of IVIg was proposed with uniformly favorable results 10,11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…but to date no case of SJS has been related to this infectious agent [18]. However, a relationship between viral infections and the simultaneous or subsequent development of drug-induced hypersensitivity has been observed in a number of clinical situations, while the full cascade of events leading from viral infections to the development of this exfoliative situation in human's remains poorly understood [19,20]. In this study we have tried to establish a possible association between HCMV and SJS/TEN suggested possibly by a temporal clinical relationship.…”
Section: Immunological Parameters In Patients With Hcmv Associated Sjmentioning
confidence: 99%
“…As manifestações cutâneas são raras e, quando presentes, têm um polimorfismo lesional caracterizado por vesículas, nódulos, placas verrucosas ou ulcerações orais, perianais e genitais. 1,3,4 O tratamento e a profilaxia da infeção por CMV em imunodeprimidos incluem ganciclovir (iv), valganciclovir (po), foscarnet (iv) ou cidofovir (iv). 1,5,6 Apresentamos o caso de uma doente com síndrome de imunodeficiência adquirida (SIDA), gravemente imunodeprimida, com ulcerações extensas provocadas por CMV.…”
Section: Introductionunclassified